2013
DOI: 10.1021/cb400161g
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of an A2-Type Modular Polyketide Synthase Ketoreductase Reveal Features Controlling α-Substituent Stereochemistry

Abstract: Modular polyketide synthase ketoreductases often set two stereocenters when reducing intermediates in the biosynthesis of a complex polyketide. Here we report the 2.60 Å-resolution structure of an A2-type ketoreductase from the eleventh module of the amphotericin polyketide synthase that sets a combination of l-α-methyl and l-β-hydroxyl stereochemistries and represents the final catalytically-competent ketoreductase type to be structurally elucidated. Through structure-guided mutagenesis a double mutant of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(97 citation statements)
references
References 35 publications
6
91
0
Order By: Relevance
“…KRs catalyze the reduction of C3 keto groups of polyketide intermediates carried by ACPs to hydroxyl groups utilizing the NADPH coenzyme (Zheng et al, 2013). In hybrid modules generated by domain exchange, KRs usually retain their native stereospecificity, suggesting that stereocontrol of reduced hydroxyl groups is intrinsic to individual KR domains (Kao et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…KRs catalyze the reduction of C3 keto groups of polyketide intermediates carried by ACPs to hydroxyl groups utilizing the NADPH coenzyme (Zheng et al, 2013). In hybrid modules generated by domain exchange, KRs usually retain their native stereospecificity, suggesting that stereocontrol of reduced hydroxyl groups is intrinsic to individual KR domains (Kao et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Crystal structures of all four types of KR have been solved to elucidate the stereocontrol of KR domains (Keatinge-Clay, 2007; Keatinge-Clay and Stroud, 2006; Zheng et al, 2013; Zheng et al, 2010). KRs belong to the short chain dehydrogenase/reductase (SDR) superfamily.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies both in vitro 51 and in vivo 52 on KRs sourced from multiple PKSs have conclusively demonstrated their intrinsic epimerase activity. Despite the resolution of seven KR structures [29][30][31][32][33][34][35] , however, multiple aspects of the mechanism remain unclear. For example, although specific active site sequence motifs correlate well with the direction of ketoreduction (whether A-or B-type) 53,54 , how and whether these residues participate in guiding the substrate into one side or the other of the active site has been unclear.…”
Section: The Dissection Approach To Studying Functional Domainsmentioning
confidence: 99%
“…This motif is absent from A-type ketoreductases that form 3L-3-hydroxyacyl-ACP intermediates. Ketoreductase domains also determine methyl stereochemistry after incorporation of branched extenders (Weissman et al, 1997;Valenzano et al, 2009;Zheng et al, 2013;Annaval et al, 2015). Additional amino acid residues have been identified that allow prediction of C-2 methyl as well as C-3 alcohol stereochemistry in an extended chain (Keatinge-Clay, 2007).…”
Section: Polyene Biosynthesis and Polyketide Stereochemistrymentioning
confidence: 99%
“…Crystal structures have now been determined for seven PKS KR domains, including the A1 KR2 and A2 KR11 domains of the amphotericin PKS (Bonnett et al, 2013). These structural studies have given insights into how PKSs determine hydroxyl and methyl stereochemistry (Zheng et al, 2013;Keatinge-Clay 2016). Where a 2-methyl-3-ketoacyl intermediate is fully processed, the chirality at C-2 is determined by the enoylreductase domain.…”
Section: Polyene Biosynthesis and Polyketide Stereochemistrymentioning
confidence: 99%